URGENSI PENDIDIKAN PRA NIKAH - Amin, M. Misbahul; Diana Dewi Roihatul Jannah (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2025)
Pre-marital education in Indonesia has become increasingly urgent in light of rising rates of early marriage, divorce, and domestic violence. Data indicates that many prospective couples lack an understanding of their rights and responsibilities in marriage, as well as the challenges they will face. This study aims to explore the necessity of pre-marital education as a preventive solution and to evaluate the effectiveness of existing programs. Through a qualitative approach, this article analyzes the needs and challenges associated with pre-marital education and provides policy recommendations for the government and stakeholders to improve the implementation of pre-marital education. The findings highlight that evaluating the material, methods, and accessibility of pre-marital education is crucial to achieving the goal of enhancing family well-being and preventing early marriage. It is hoped that with the strengthening of pre-marital education, young couples in Indonesia will be better prepared to build harmonious and prosperous family lives.